The Influence of Psychological Factors in Purchase Decision among College Students: Empirical Evidence From Electronic Product Market In Jakarta, Indonesia - Nurcahyo, Bagus (Archives of Business Research, 2016)
Psychological factors are very important because it is a central activity that affect the consumer in making the decision to choose a product. Psychological factors thought to affect purchasing decisions is motivation, perception, learning, belief, and attitude. This study aims to analyze the influence of psychological factors of motivation, perception, learning, beliefs, and attitudes in purchase decision for electronic product among the students college. The data used are primary data that was measured using a questionnaire statement. Total questionner predetermined 200 respondents. The results of these studies show that psicological factor consist of motivation, perception, and learning influence consumers in the form of beliefs, belief affects the attitude of a consumer in purchase decision among the college students.